Cost and Time Analysis Using the Earned Value Analysis Method - Sugeng Hariyadi; Hanie Teki Tjendani; Budi Witjaksana (Green Publisher Indonesia, 2024)
Construction project management prioritizes the achievement of three main objectives: cost, quality, and time. This study evaluates a road widening project in Mojokerto Regency with a target completion time of 150 days. To prevent delays and cost overruns, researchers used the Earned Value method to identify early warnings regarding project performance. This method integrates time and cost values through measurements of Cost Variance (CV), Schedule Variance (SV), Cost Performance Index (CPI), Schedule Performance Index (SPI), Estimated at Completion (EAC), and Estimated Schedule at Completion (EAC). The research findings show that additional costs required (ETC) reached Rp 3,276,704,110.14, with additional time (ETS) up to week 12 being 87 days. The change in project costs (EAC) reached Rp 3,961,767,811.01 from the contract cost, while the project completion time (EAS) was 171 days. The analysis indicates that the construction service provider has implemented an efficient implementation method with consistent supervision, ensuring the smooth progress of the project.